Literacy in sexual and reproductive health and sexual behavior in young adult: - Amaro-Hinojosa , Marily Daniela (2025)
Introduction: Health literacy is key to the prevention and promotion of safe sexual behaviors to allow a decrease in the number of unplanned pregnancies and sexually transmitted infections among young people, situations that are considered public health issues. Objective: Describe the sexual behavior and sexual and reproductive health literacy among young people, compare sexual and reproductive health literacy by sex and sexual behavior, and examine the relationship between sexual and reproductive health literacy and the sexual behavior of young people.2Material and methods: The study design was descriptive, correlational and cross-sectional; the sample consisted of 622 young people from Mexico, selected at convenience. Data collection was performed through the Google Forms platform. Results: 83.6% of the participants had initiated a sexual life. The main sexual behaviors practiced by these young people include petting, watching pornography and masturbation; 52.9% reported that they changed condoms when they were going to have more than one type of sexual intercourse. The median sexual literacy in sexual and reproductive health was 48. Women had higher literacy scores than men as well as those who practiced petting and those who changed condoms when having more than one type of sexual intercourse. No relationship was found between sexual and reproductive health literacy and sexual behaviors.Conclusion: Young people show low sexual and reproductive literacy and engage in non-penetrative sexual behaviors. Although literacy is not related to sexual behavior, other factors are related such as age and sexual debut.